Utilization-focused evaluation for agricultural innovation - Patton, Michael Quinn; Horton, D (CGIAR, 2009)
Utilization-focused evaluation (UFE) is based on the principle that an evaluation should be judged by its utility. So no matter how technica lly sound and methodologically elegant, an evaluation is not truly a g ood evaluation unless the findings are used. UFE is a framework for en hancing the likelihood that evaluation findings will be used and lesso ns will be learnt from the evaluation process. This Brief, based on th e book Utilization-focused evaluation, introduces this approach to eva luation, outlines key steps in the evaluation process, identifies some of the main benefits of UFE, and provides two examples of UFE in the context of programmes aimed at promoting agricultural innovation.